2023
DOI: 10.1037/int0000292
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect processes and posttraumatic stress disorder symptoms: Findings from an open label and uncontrolled pilot study using the positive memory processing technique.

Abstract: Recently, a five-session processing of positive memories technique (PPMT) was proposed as a novel intervention for posttraumatic stress disorder (PTSD). One purported outcome of and mechanism underlying PPMT’s effects on PTSD is improved positive affect processes. In this uncontrolled pilot study, we examined whether PPMT was associated with decreases in PTSD severity; and whether changes in positive affect levels, reactivity, and dysregulation related to changes in PTSD severity across sessions. The sample in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
1
0
0
Order By: Relevance
“…These results are consistent with prior observational research using an ESM design over varied periods of time, including 10 days in a student sample (Contractor, Messman, et al, 2023a), 28 days in a veteran sample (Possemato et al, 2012), and 15 days in a sample of service members (Biggs et al, 2019). Our results may indicate unintended effects of retrieving positive memories daily on PTSD symptoms, consistent with literature suggesting that the retrieval and processing of positive memories repeatedly may improve posttrauma well-being (Contractor, Banducci, et al, 2020; Contractor, Slavish, et al, 2023b; Contractor, Weiss, et al, 2022; Miguel-Alvaro et al, 2021). Results may also reflect more accurate reporting of daily PTSD symptoms within an ESM framework compared to what we see with retrospective reports (Schuler et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with prior observational research using an ESM design over varied periods of time, including 10 days in a student sample (Contractor, Messman, et al, 2023a), 28 days in a veteran sample (Possemato et al, 2012), and 15 days in a sample of service members (Biggs et al, 2019). Our results may indicate unintended effects of retrieving positive memories daily on PTSD symptoms, consistent with literature suggesting that the retrieval and processing of positive memories repeatedly may improve posttrauma well-being (Contractor, Banducci, et al, 2020; Contractor, Slavish, et al, 2023b; Contractor, Weiss, et al, 2022; Miguel-Alvaro et al, 2021). Results may also reflect more accurate reporting of daily PTSD symptoms within an ESM framework compared to what we see with retrospective reports (Schuler et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In the second study, authors found that survivors of trauma who repeatedly retrieved positive (and neutral) memories reported less PTSD and depression severity, fewer posttrauma cognitions, and improved affect [39]. Using an open-label pilot trial, the feasibility and effects of the 5-session PPMT were examined among 12 survivors of trauma [40,41]. The authors found that PPMT reduced PTSD symptoms, reduced negative affect, and improved regulation of positive affect, and there were good feasibility indicators for PPMT (eg, PPMT was acceptable).…”
Section: Introductionmentioning
confidence: 99%